Educational Values Found in the “Trolls” Animation Movie 2016 - Arwati, Ni Kadek Dewi; Sulatra, I Komang; Suastini, Ni Wayan (Journal of Language and Applied Linguistics, 2023)
The study aims to find out educational values and also how those values are reflected by the characters in the movie. The value of educational fosters us into adult individuals, individuals who are able to plan the future and make the right decisions in life. In this life of course having a noble character will look good in the community. The researcher used movie to analyse because when we watch movies, we not only get entertainment but we also get lessons or educational values tucked in the film. This study used theory of Linda and Eyre (1997) and theory of Klarer (1998). This study uses descriptive qualitative method. The result of this study indicated: (1.) Educational values found in Trolls movie (2016) are value of being consist of bravely, peacefulness, responsibility, honest. Values of giving consist of religious, tolerance/respect, social care, kind & friendly. (2.) Those values are reflected by the six characters in the movie. Value of being consists of three characters with six data, values of giving is consisting of four characters with four data. Those educational values were presented through conversation and action in the movie.